AREAS OF IMPROVEMENT OF STATE MANAGEMENT OF FINANCIAL AND ECONOMIC SECURITY OF UKRAINE IN MODERN CONDITIONS - Maystro S.V. (Pressing Problems of Public Administration, 2015)
We consider the level of financial and economic security of Ukraine. Directions improvement of state management of financial and economic security of Ukraine in modern conditions.